Sources of Variation in Social Plasticity in Female Mate Preferences and Male Traits - (:unkn) unknown (My University, 2018)
Female preferences are an important cause of selection on male traits, and exploring the sources of variation in these preferences has been the focus of intense behavioral research. This is due to the fact that understanding this variation is integral to understating the maintenance of variation and complexity in male traits, as well as the evolution and divergence of populations. This project aims to explore the sources of variation in these mating preferences, as well as examine whether similar sources affect components of male traits. This was accomplished using the well-studied mating system of the Green Treefrog, Hyla cinerea that features female preferences for the male advertisement call. Using playback experiments, I dissect the constituent parts of female preferences – preference functions and choosiness, and demonstrate that sources of variation in preferences can be due to interactions between choosiness and social experience, as well as interactions between female body size and the shape of a female’s preference function and the constituent traits of the preference function curve. Further, I demonstrate that social experience also affects the male trait, and can drive variation in the presentation of advertisement calls. This work demonstrates that while sexual selection can be a strong and directional driver of the evolution of mating behaviors, substantial variation can arise from a number of sources that may have profound effects for the evolution of species.
Keywords: Behavioral Ecology; Choosiness; Female Preferences; Sexual Selection; Social Plasticity